2005
DOI: 10.1038/nature03481
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the social amoeba Dictyostelium discoideum

Abstract: The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes encode ~12,500 predicted proteins, a high proportion of which have long repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
1,190
3
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,175 publications
(1,230 citation statements)
references
References 98 publications
22
1,190
3
15
Order By: Relevance
“…The size distribution showed distinct peaks at 21 nt of near equal proportion of reads from both wt and drnB - strains (Figure 1(a)). No large difference was observed for 21 nt sequences matching mRNA (sense and antisense) or non-coding RNAs (ncRNAs) such as tRNAs, rRNAs, small nucleolar RNAs (snoRNAs), spliceosomal RNAs (snRNAs), single recognition particle RNAs (SRP RNAs) or Class I RNAs (Figure 1(b)) [22,26,3436]. The great majority of the 21 nt RNAs from both wt and drnB - strains (68,4% and 67,2%, respectively) derive from the retrotransposon element DIRS-1, which also may function as centromeres in D. discoideum [37,38].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The size distribution showed distinct peaks at 21 nt of near equal proportion of reads from both wt and drnB - strains (Figure 1(a)). No large difference was observed for 21 nt sequences matching mRNA (sense and antisense) or non-coding RNAs (ncRNAs) such as tRNAs, rRNAs, small nucleolar RNAs (snoRNAs), spliceosomal RNAs (snRNAs), single recognition particle RNAs (SRP RNAs) or Class I RNAs (Figure 1(b)) [22,26,3436]. The great majority of the 21 nt RNAs from both wt and drnB - strains (68,4% and 67,2%, respectively) derive from the retrotransposon element DIRS-1, which also may function as centromeres in D. discoideum [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…First, a recent report by Kruse et al indicated that mir-1176 and mir-1177 are dependent on RNA polymerase II (RNA Pol II) transcription [30], suggesting that pri-miRNA transcripts in D. discoideum may be polyadenylated as has been demonstrated in animals and plants [4,5,49]. Secondly, the genome of D. discoideum is very AT-rich (about 78%) [26], where long stretches of As are common within transcripts and therefore most likely allow for selection of RNAs with internal poly(A)-tracts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations